2020
DOI: 10.1074/jbc.ra119.008703
|View full text |Cite
|
Sign up to set email alerts
|

Galectin 3–binding protein suppresses amyloid-β production by modulating β-cleavage of amyloid precursor protein

Abstract: Alzheimer's disease (AD) is the most common type of dementia, and its pathogenesis is associated with accumulation of β-amyloid (Aβ) peptides. Aβ is produced from amyloid precursor protein (APP) that is sequentially cleaved by β- and γ-secretases. Therefore, APP processing has been a target in therapeutic strategies for managing AD; however, no effective treatment of AD patients is currently available. Here, to identify endogenous factors that modulate Aβ production, we performed a gene microarray–based transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…The protein Gal-3BP is associated with the immune system [94], as it functions as a suppressor of inflammatory responses by blocking the NF-kB signalling pathway. Remarkably, Gal-3BP can suppress Aβ production through inhibition of the amyloid precursor protein (APP) processing by β-secretase [95]. Thus, the delivery of Gal-3BP into neurons and microglia in the brain through IN administration of EVs might be beneficial for restraining neuroinflammation and reducing amyloid-beta (Aβ) plaques in AD.…”
Section: Discussionmentioning
confidence: 99%
“…The protein Gal-3BP is associated with the immune system [94], as it functions as a suppressor of inflammatory responses by blocking the NF-kB signalling pathway. Remarkably, Gal-3BP can suppress Aβ production through inhibition of the amyloid precursor protein (APP) processing by β-secretase [95]. Thus, the delivery of Gal-3BP into neurons and microglia in the brain through IN administration of EVs might be beneficial for restraining neuroinflammation and reducing amyloid-beta (Aβ) plaques in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Galectin-3-binding protein (G3BP) was just recently shown to inhibit the processing of APP into Aβ by direct interaction with APP [ 299 ]. Co-deposition of G3BP in senile plaque may be a consequence of this interaction but it could also result in reduced inhibitory capacity and thereby a positive feedback loop for Aβ production.…”
Section: Survey Of Extracellular Proteins That Associate With Aβmentioning
confidence: 99%
“…GPLD1 gene has been reported to interact with Apolipoprotein A1 and APOA4 (Deeg et al, 2001) and Lin et al, 2015 have shown that the low levels of APOA1 , APOC3 , and APOA4 are associated with risk of AD. Importantly, the GPLD1 is a candidate gene that modulates Aβ production (Seki et al, 2020). Wilmsdorff et al, (2013) reported that the increased SLC1A3 expression indicates facilitated transport and may result in reduced glutamate neurotransmission.…”
Section: Discussionmentioning
confidence: 99%